Streptococcus pneumoniae meningitis in a child with idiopathic nephrotic syndrome: a case report - David Guernsey; Aparna Arun; Rabia Agha; Juan C. Kupferman (Journal of Medical Case Reports, 2022)
Abstract Background Children with nephrotic syndrome are at increased risk of infections, including bacterial peritonitis, pneumonia, and cellulitis. However, bacterial meningitis, a potentially life-threatening complication, has not been highlighted as an infectious complication of nephrotic syndrome in recent reviews. We report a very subtle and unusual presentation of bacterial meningitis in a child with nephrotic syndrome, which without a high index of suspicion, would have been missed. Case presentation A 9-year-old African-American male with a history of steroid-dependent nephrotic syndrome presented to the nephrology clinic for routine follow-up. His medications included mycophenolate mofetil and alternate-day steroids. His only complaint was neck pain and stiffness that the mother attributed to muscle tightness relieved by massage. There was no history of fever, vomiting, headache, photophobia, or altered mental status. On physical examination, he was afebrile (99 °F), but had mild periorbital swelling and edema on lower extremities. He appeared ill and exhibited neck rigidity, and demonstrated reflex knee flexion when the neck was bent. Laboratory evaluation revealed leukocytosis, elevated C-reactive protein, hypoalbuminemia, and proteinuria. Cerebrospinal fluid suggested bacterial meningitis. The patient was treated with ceftriaxone and vancomycin. Both cerebrospinal and blood cultures grew Streptococcus pneumoniae; vancomycin was discontinued. The child completed a 2-week course of ceftriaxone and was discharged home. Conclusions A high index of suspicion is necessary in children with nephrotic syndrome treated with corticosteroids, as symptoms may be masked, and thus, a life-threatening disease be missed. Bacterial meningitis should be highlighted as a serious infection complication in children with nephrotic syndrome.